German ways of war : the affective geographies and generic transformations of German war films - Fisher, Jaimey (War culture., 2022)
"German Ways of War deploys theories of space, mobility, and affect to investigate how war films realize their political projects. Analyzing films across the decades, from the 1910s to 2000s, German Ways of War addresses an important lacuna in media studies: while scholars have tended to focus on the similarities between cinematic looking and weaponized targeting -- between shooting a camera and discharging a gun -- this book argues that war films negotiate spaces throughout that frame their violence in ways more revealing than their battle scenes. Beyond that well-known intersection of visuality and violence, German Ways of War explores how the genre frames violence within spatio-affective operations. The production of novel spaces and evocation of new affects transform war films, including the genre's manipulation of mobility, landscape, territory, scales, and topological networks. Such effects amount to what author Jaimey Fisher terms the films' "affective geographies" that interweave narrative-generated affects, spatial depictions, and political processes"--